Utilization of the Education Management Information System (EMIS) as a Decision Making Means in the Institutional Section of the Regional Office of the Ministry of Religion, Yogyakarta Special Region - Luhur Arroyan; Nurlaila Subekti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
This study was conducted to determine the utilization of the education management information system (EMIS) as a means of decision making in the institutional section at the Regional Office of the Ministry of Religion, Yogyakarta Special Region.This research is a qualitative research using data collection techniques in the form of interviews, observations, and documentation. Technical analysis of data using data reduction, data presentation, and drawing conclusions. This research focuses on objective results with research subjects who really know, experience, and understand in this case the head of the madrasa education sector, along with the operator and the head of the SIM institutional section. The results of the study show that the basis for decision making can be completed because it has been accumulated by regulations and adopted the opinion of top managers. If the alternative answers are not satisfactory, the analysis will continue with deliberation with stakeholders and elements of the madrasa.Decision-making and Utilization of EMIS data during the study showed that EMIS plays a role in the distribution of the budget contained in the PIP program (smart Indonesia program), Madrasah BOS, National Examination student data, transfer and appointment of principals, equitable distribution of teachers and madrasa infrastructure, and the contribution of data The EMIS is utilized by the People's and Community Welfare Bureau, and the Provincial Government Legal Bureau. In addition, EMIS also plays a role in providing infrastructure assistance. EMIS development needs to be improved with new innovations. Data updates must be done frequently, always input as long as there are dynamics of data changes so that they are up to date. Reports on development, development, performance improvement should be based on EMIS data. The dynamics in society continue to exist at all times, for example there are students who move, teachers who transfer, teachers who are appointed as acting. Then EMIS must be updated every day.